2017
DOI: 10.3171/2016.9.peds16275
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing outcomes of the treatment of positional plagiocephaly in infants: a 7-year experience

Abstract: OBJECTIVE Following institution of the Back to Sleep Campaign, the incidence of sudden infant death syndrome decreased while the prevalence of positional skull deformation increased dramatically. The management of positional deformity is controversial, and treatment recommendations and outcomes reporting are variable. The authors reviewed their institutional experience (2008–2014) with the treatment of positional plagiocephaly to explore factors associated with measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 19 publications
1
17
0
1
Order By: Relevance
“…For infants beginning treatment between 3.0 and 4.5 months of age, reduction in cephalic index was 5.1%; for infants 4.5 to 6.0 months of age, it was 3.2%; and for infants entering treatment later than 6 months, reduction in cephalic index was 2.9%. These results mirror the findings of other investigators who have previously reported on the positive impact of early entrance age on the effectiveness of the cranial orthosis 37 , 44 - 52 ( Table 6 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…For infants beginning treatment between 3.0 and 4.5 months of age, reduction in cephalic index was 5.1%; for infants 4.5 to 6.0 months of age, it was 3.2%; and for infants entering treatment later than 6 months, reduction in cephalic index was 2.9%. These results mirror the findings of other investigators who have previously reported on the positive impact of early entrance age on the effectiveness of the cranial orthosis 37 , 44 - 52 ( Table 6 ).…”
Section: Discussionsupporting
confidence: 91%
“…The most immediate limitation is that this is not, nor was it designed to be, a randomized control trial. While many authors have previously discussed why execution of a randomized control trial may be difficult or even ethically questionable, 52 - 54 it was simply not within our scope to be able to perform. As a medical treatment provider, patients are sent by physicians who have diagnosed and monitored their patients and have prescribed treatment based on their dissatisfaction with the progression of head shape.…”
Section: Discussionmentioning
confidence: 99%
“…(See Fig. 2 in the related article by Lam et al 8 ). We included patients younger than 12 months of age at presentation with a diagnosis of occipital brachycephaly, occipital plagiocephaly, or both, who had a documented recommended treatment plan.…”
Section: Resultsmentioning
confidence: 99%
“…Adherence was recorded according to parental report on details of treatment at the time of each clinic visit. Our treatment algorithm and rationale are described in a related paper by Lam et al 8 This study received approval from the Baylor College of Medicine institutional review board.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation